PEMBERDAYAAN KELOMPOK TANI UNTUK MENGAKTIFKAN RUMAH KOMPOS DI DESA JELBUK MELALUI PRODUKSI PUPUK BOKASHI - Widya Kristiyanti Putri; Susan Barbara Patricia; Diana Fauziyah; Hilmi Tsabiatul Azmi; Yusuf Dary Ahnaf; Iqbal Tri Pamungkas; Joni Murti Mulyo Aji (Universitas Mataram, 2023)
Farmers’ dependence on the use of inorganic fertilizers triggers a new problem when the rise in inorganic fertilizer prices happened because Indonesia’s government remove the subsidy for some fertilizers. The farmers in Jelbuk village, Jember district has abundant cow dung from their husbandry waste. An amount of 129 cows are potential husbandry for Baru Muncul Farmers Group aside from their farming daily activities. The waste could be the main ingredient for bokashi compost fertilizer. Jelbuk village also has a compost house that hasn’t been used yet since 2017. This community service aims to activate the compost house by using potential waste from cow dung. This activity was conducted in some stages sequentially socializing, training, making compost, Focus Group Discussion (FGD), and compost application. All stages were well followed by Baru Muncul farmers, from socializing to compost application on pakcoy mustard. Finally, the compost house becomes active again and is used by Jelbuk’s villagers as a fertilizer processing place.